Uji Aktivitas Antibakteri dan Antikuorum Sensing Fraksi dari Ekstrak Etanol Daun Salam (Eugenia polyantha Wight.) - Ardani, Yonas Bianityo; Soegianto, Lisa; Wijaya, Sumi (Jurnal Farmasi Sains dan Terapan, 2013)
Eugenia polyantha is being used as empirical plant for antiseptic, anthelmintic, anesthetic, keratolytic and also has properties protein in bacterial cells. The antibacterial activity of extract of Eugenia polyantha has been proved in previous study, therefore this research was conducted to know the antibacterial and antiquorum sensing from fractions of ethanolic extract of Eugenia polyantha. The extraction was prepared by maceration and fraction was prepared by liquid-liquid fractionation method with n-hexane (non polar), ethyl acetate (semipolar) and water (polar). Bioautography method with thin layer chromatography and chloroform as mobile phase was conducted to determine the active fraction. The diameter of inhibition zone was measured or determined by diffusion method, while concentration of minimum inhibition (MIC) and bactericidal concentration (MBC) were determined using broth and agar dilution methods. Antiquorum sensing activity for P. aeruginosa was carried on, using pigment survey and motility method The antibacterial activities showed that ethyl acetate fraction 2596 gave diameter of growth inhibition zone greater than others, 1:1.48 mm against S. aureus and 9.03 mm against P. aeruginosa. The MIC of ethyl acetate fraction gave value of :1.56% against S. aureus and 12.5% against P. Aeruginosa, meanwhile the MBC was 3.1396 against S. aureus and more than 12.5% against P. aeruginosa. The result showed that ethyl acetate fraction has potential antiquorum sensing activity on concentration of 2.5 %. The active fraction of ethanolic extract of Eugenia polyantha which has antibacterial and antiquorum sensing activity was ethyl acetate fraction.